Предмет: Алгебра,
автор: kazakovaleyla
Найти производные :
1)y=e^5x+2 sin^4 5x
2)y=ln(3x^2-tg2x)
3)2y•lny=x
Ответы
Автор ответа:
0
Найти производные :
1)y=e^5x+2 sin^4 5x
2)y=ln(3x^2-tg2x)
3)2y•lny=x
Решение
1) y' = (e^5x+2 sin^4(5x))' = (e^5x)'+ (2 sin^4(5x))' = 5*e^(5x) +2*4sin^3(5x)*cos(5x)*5=
= 5*e^(5x) + 40sin^3(5x)*cos(5x)
2) y' = (ln(3x^2-tg2x))' = (1/(3x^2-tg2x))*(3*2x-(1/cos^2(2x))*2) =
= (6x-2/cos^2(2x))/(3x^2-tg2x)
3) 2y•lny = x
Дифференцируем каждую часть уравнения отдельно а потом находим у'
(2y•lny)' = 2y' * ln(y) + 2y* (1/y)*y' = 2y' *ln(y)+2y' = 2y'(ln(y)+1)
x' =1
2y'(ln(y)+1)=1
y' = 1/(2(ln(y)+1))
1)y=e^5x+2 sin^4 5x
2)y=ln(3x^2-tg2x)
3)2y•lny=x
Решение
1) y' = (e^5x+2 sin^4(5x))' = (e^5x)'+ (2 sin^4(5x))' = 5*e^(5x) +2*4sin^3(5x)*cos(5x)*5=
= 5*e^(5x) + 40sin^3(5x)*cos(5x)
2) y' = (ln(3x^2-tg2x))' = (1/(3x^2-tg2x))*(3*2x-(1/cos^2(2x))*2) =
= (6x-2/cos^2(2x))/(3x^2-tg2x)
3) 2y•lny = x
Дифференцируем каждую часть уравнения отдельно а потом находим у'
(2y•lny)' = 2y' * ln(y) + 2y* (1/y)*y' = 2y' *ln(y)+2y' = 2y'(ln(y)+1)
x' =1
2y'(ln(y)+1)=1
y' = 1/(2(ln(y)+1))
Похожие вопросы
Предмет: Биология,
автор: alisakoltashina36
Предмет: Литература,
автор: dema226
Предмет: Химия,
автор: 3324135
Предмет: Математика,
автор: Kora10